Finding the hardcore roots : early post-soca tendencies in Caribbean music - Best, Curwen (2001)
Discusses the early evolution of the 1990s post-soca dance music called ringbang. Traces the roots of this new style back to the early 1980s and analyses how it began to diverge from mainstream soca of the time. Suggests that the evolution of post-soca styles owes much to the impact of new music technologies on Caribbean culture.